The Effect of Four Commonly Used Root Conditioner Agents in Different Time Periods Applied on Periodontally Diseased and Healthy Teeth - Torkzaban P; Seyedzadeh Sabounchi S (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Root surface contamination or infection can potentially change the consequences of regenerative periodontal therapies and therefore the modification and disinfection of the contaminated root surfaces are necessary. Objectives: This study aimed to compare the surface characteristics of the extracted human teeth after exposure to four root conditioners in different time periods. Materials and Methods: The study samples were prepared from 40 freshly extracted teeth including 20 affected teeth with periodontal diseases and 20 healthy teeth. After performing root planning, 240 dentinal block samples were prepared and each affected and healthy sample was randomly allocated to receive one of the following root conditioners; Ethylenediaminetetraaceti acid (EDTA), citric acid, doxycycline, and tetracycline or rinsed with normal saline as the control agent. The prepared specimens were evaluated using scanning electron microscope and the inter-group differences and changes in study indices; dentin (%), tubular spaces (%), and diameter of dentinal tubules (μm²) were compared using one-way ANOVA test. Results: In the control group receiving normal saline, the changes in the indicators of dentin, tubular spaces, and diameter of dentinal tubules remained insignificant in all time periods. EDTA, citric acid, and tetracycline had chelating effects on the study indices; however, doxycycline led to gradual decrease of the tubular space and diameter as well as increase in dentin percentage. Conclusions: In different time intervals and when considering healthy or affected tooth surfaces, the effect of conditioning agents could be different. Amongst the four agents used, EDTA and tetracycline consistently increased the diameter of tubules and percentage of patent tubules in both healthy and diseased teeth.